Supernatural vanishings : otherworldly disappearances - Davies, Rodney (New York : Sterling Publishing, 1996)
Personen, dieren of voorwerpen die opeens verdwijnen: het blijft een boeiende materie.
Includes index.
Originally published: Supernatural disappearances. London : R. Hale, c1995.
Keywords: Astral projection; Bilocation; Disappearances (Parapsychology).